A lot like love - Snow, Jennifer (Amara, is an imprint of Entangled Publishing, LLC, 2021)
"When Sarah Lewis inherits a run-down B&B from her late grandmother...she feels a sense of obligation to her grandmother to get it back to the landmark tourist destination it once was...even if that means hiring the best contractor for the job, who happens to be her old high school crush...As they spend more time together...the spark between them ignites. But will saving the B&B be enough to convince them both to take a second chance at love?"--